2015
DOI: 10.1016/j.apm.2015.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of injector needle movement and the nozzle inclination angle on the internal fluid flow and spray structure of a group-hole nozzle layout

Abstract: a b s t r a c tIn this study, we explored the spray behavior as a result of microscopic variations in the flow characteristics when the nozzle hole inclination angle was varied and the needle reciprocated. The volume fraction and viscosity contours were investigated at three needle modes of 0.01, 0.25, and 0.24 mm using three nozzle inclination angles of 10°, 15°, and 30°. We determined the relationship between the two key parameters of liquid viscosity (which developed in the sac-volume and nozzles) and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Error and uncertainty analysis. The errors and uncertainties originate from the instruments, environment, operating condition, results and analysis method, results and analysis tools and processes, and the changes in the angle of inclination of the fuel spray central axis 46,49 . The errors and uncertainties from the environment and operating conditions could be neglected because the environment and operating conditions in the experiment process were aligned.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Error and uncertainty analysis. The errors and uncertainties originate from the instruments, environment, operating condition, results and analysis method, results and analysis tools and processes, and the changes in the angle of inclination of the fuel spray central axis 46,49 . The errors and uncertainties from the environment and operating conditions could be neglected because the environment and operating conditions in the experiment process were aligned.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…In addition, the error bars of the macroscopic spray characteristics also contained changes in the angle of inclination of the fuel sprays central axis against the geometrical axis of the nozzle hole 50 . The angle changes depended on cavitation and were affected by fuel properties 49,51 . However, the slight differences in fuel properties have no impact on cavitation.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…Aside from altering nozzle exit velocities [13], this could also alter the nozzle needle lift profile particularly affecting the initial opening and closing transients [13,21]. Hole number and hole position have also been shown to strongly influence spray stability and near field spray breakup [13,18,20,21]. This influence is thought to arise from modification to the internal flow structure which accompanies change to these parameters.…”
Section: Introductionmentioning
confidence: 92%
“…A group-hole nozzle (GHN) is a variation of this design, in which rather than being uniformly spaced, the nozzle holes are spaced closely together to form a group, with the groups, if more than one, being spaced around the tip. Because of their potential benefits to fuel consumption and emissions [16], GHNs, particularly in the form of a twin-hole nozzle (THN), have recently been a focus of interest [9,10,[16][17][18][19][20]. An important feature of GHNs is they enhance spray to spray interaction whether through direct merging of closely spaced sprays [9], or indirectly through modification to air entrainment into individual but unmerged sprays as they compete for the surrounding air.…”
Section: Introductionmentioning
confidence: 98%
“…Fuel injection process plays a major role in many aspects of combustion performance. The influence of nozzle structure is remarkable on the atomization performance [19][20][21][22]. With the progress of technology [23], it is found that the properties of breakup morphology and fragment distribution in different regimes are different [24][25][26][27][28].…”
Section: Primary Atomizationmentioning
confidence: 99%